PD/1-PD-Ls Checkpoint: Insight on the Potential Role of NK Cells - Pesce, Silvia; Greppi, Marco; Grossi, Francesco; Del Zotto, Genny; Moretta, Lorenzo; Sivori, Simona; Genova, Carlo; Marcenaro, Emanuela (Frontiers in Immunology, 2019)
The identification of inhibitory NK cell receptors specific for HLA-I molecules (KIRs and NKG2A) provided the molecular basis for clarifying the mechanism by which NK cells kill transformed cells while sparing normal cells. The direct interactions between inhibitory NK cell receptors and their HLA-I ligands enable NK cells to distinguish healthy from transformed cells, which frequently show an altered expression of HLA-I molecules. Indeed, NK cells can kill cancer cells that have lost, or underexpress, HLA-I molecules, but not cells maintaining their expression. In this last case, it is possible to use anti-KIR or anti-NKG2A monoclonal antibodies to block the inhibitory signals generated by these receptors and to restore the anti-tumor NK cell activity. These treatments fall within the context of the new immunotherapeutic strategies known as “immune checkpoint blockade”. These antibodies are currently used in clinical trials in the treatment of both hematological and solid tumors. However, a more complex scenario has recently emerged. For example, NK cells can also express additional immune checkpoints, including PD-1, that was originally described on T lymphocytes and whose ligands (PD-Ls) are usually overexpressed on tumor cells. Thus, it appears that the activation of NK cells and their potentially harmful effector functions are under the control of different immune checkpoints and their simultaneous expression could provide additional levels of suppression to anti-tumor NK cell responses. This review is focused on PD-1 immune checkpoint in NK cells, its potential role in immunosuppression, and the therapeutic strategies to recover NK cell cytotoxicity and anti-tumor effect.